Informatics Engineering Students’ Competence in English: Formative and Summative Assessment - Andi Idayani (Fakultas Keguruan dan Ilmu Pendidikan (FKIP), Universitas Lancang Kuning, 2021)
Assessment is the ways of teachers/lecturers gather data about their teaching and their students’ learning. In order to grapple with what seems to be an over use of testing, educators should frame their view of testing as assessment and that assessment is information. In relation to this, the researcher interested in conducting a study which is focus on assessing Informatics Engineering students’ competence in English. The researcher used descriptive research. The population of the reaserch was the informatics Engineering students which total students was 160 students at the second semester. Purposive sampling used in this study in order to focus the finding which the number of sample was 40 students. This study used formative and summative assessment in assessing students’ comptence in English. Following that, the data was collected during teaching and learning process in form of observation, documentation, and test. After that, the data was analyzed by using statistical in term of norm-references and criterion-references. Based on the result of this study, it could be concluded that the formative assessment format mostly designed in speaking and listening test format and summative assessment was applied all in English skills format since the lecturer consider that it is beneficial for students to master the particular skills as the requirements for applying into their careers.